Bimtek Penyusunan Instrumen Asesmen 7C dan Asesmen Higher Order Thinking Skills (HOTS) Bagi Asosiasi Profesi Bidang Kependidikan - Rosidin, Undang; Hasnunidah, Neni; Setiawati, Santy; Ahdiat, Mohammad (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Teachers' assessment instrument development still focuses on memorizing, understanding, and applying the skills. Evaluation questions encompass Higher Order Thinking Skills (HOTS) and the 7Cs (Critical Thinking, Collaboration, Communication, Creativity, Connectivity, Computational Thinking, and Cross-Cultural Understanding). This technical guidance aims to equip teachers with skills, update their knowledge, and train them in developing 7C and HOTS assessment instruments. The method used was technical guidance that began with a pretest, followed by material delivery, discussion, Q&A, and practice in preparing 7C and HOTS assessment instruments, as well as a posttest. This technical guidance was attended by 47 people who are members of the Indonesian Education Evaluation Association (HEPI), a professional association in the field of education. The results of the technical guidance activities showed that the increase in teachers' understanding of preparing 7C and HOTS assessment instruments was classified as moderate with an average n-gain of 0.69. The results of the n-gain data classification showed that 47% of teachers' understanding increased moderately and 53% increased significantly. Therefore, this training activity was effective in improving the understanding of 7C assessment preparation and HOTS assessment for teachers who are members of the HEPI professional association.